Визначення оптимальних умов теплообміну під час захисту поверхонь нагрівання котла - Якимів, Є.; Мисак, Й.; Івасик, Я.; Близнюк, В.; Лашковська, Н. (Видавництво Національного університету “Львівська політехніка”, 2005)
Work concerns definition of optimum conditions of heat exchange in boiler furnace which is in a reserve. During realization of analytical evaluation was determined the method of improvement of heat exchange conditions in boiler furnace is the increase of speeds of air on surfaces of metal of heat exchange elements.
Keywords: .621.187.3